Differential regulation of AKT, MAPK and GSK3? during C2-ceramide-induced neuronal death (2010)
Evidence has implicated apoptosis as a mechanism underlying cell demise in diverse neurodegenerative diseases including Parkinson's disease (PD). Endogenous toxins and other stress signals activate the sphingomyelin pathway increasing the levels of ceramide, an important regulator of cell death.In the present paper we have analysed the contribution of PI3K/AKT-GSK3? and MAPK (ERK and JNK) pathways to cell death in a catecholaminergic cell line following exposure to C2-ceramide. We also explored the potential neuroprotective action of insulin-like growth factor-1 (IGF-1) and neurotrophin-3 (NT3).We demonstrated that C2-ceramide-induced cell death is associated to an early decrease in phosphorylation (inhibition) of PI3K/AKT and ERK, followed by phosphorylation (activation) of JNK and de-phosphorylation (activation) of glycogen synthase kinase-3 beta (GSK3?). NT3 and IGF-1 increased survival at early time points, but only IGF-1 is capable to attenuate C2-ceramide-mediated neuronal death, and this neuroprotection is associated to strong and permanent activation of AKT and inhibition of GSK3?. In conclusion, C2-ceramide initiates a series of events including an early inactivation of PI3K/AKT and ERK pathways followed by activation of JNK and activation of GSK3? and neuronal death, changes that are counteracted by IGF-1. © 2010 Elsevier Inc.